1956
DOI: 10.1139/z56-037
|View full text |Cite
|
Sign up to set email alerts
|

Life History Studies on Taenia Mustelae Gmelin, 1790 and the Taxonomy of Certain Taenioid Cestodes From Mustelidae

Abstract: Taenia mustelae Gmelin, 1790 (= T. tenuicollis Rudolphi, 1819) is proposed as the valid name for the small-hooked cestode from European brown weasel, and Taenia martis (Zeder, 1803) n. comb. (= T. intermedia Rudolphi, 1810) is proposed for the large-hooked cestode from European marten. T. mustelae adults were found naturally in the short-tailed weasel, Mustela erminea, and T. martis adults in the pine marten, Martes americana in North America; the latter constitutes a new host record. Larvae were recovered fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

1959
1959
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 4 publications
5
38
0
Order By: Relevance
“…The development of the mature larva from the primary vesicle of T. twitchelli appears to follow about the same pattern as described by Freeman (1956) for the multiscolex-type larva of T. mustelae Gmelin, 1790. In fact, some of the smaller larvae of T. twitchelli, such as those from lemmings, probably would be macroscopically indistinguishable from those of T. mustelae.…”
Section: The Host Relationships Of T Twitchellisupporting
confidence: 68%
See 1 more Smart Citation
“…The development of the mature larva from the primary vesicle of T. twitchelli appears to follow about the same pattern as described by Freeman (1956) for the multiscolex-type larva of T. mustelae Gmelin, 1790. In fact, some of the smaller larvae of T. twitchelli, such as those from lemmings, probably would be macroscopically indistinguishable from those of T. mustelae.…”
Section: The Host Relationships Of T Twitchellisupporting
confidence: 68%
“…The characteristics of the rostellar hooks serve to distinguish the adult T. twitchelli from both T. mustelae Gmelin, 1790, and T. martis (Zeder, 1803), the only other species of Taenia known from mustelids in boreal regions (cf. Freeman, 1956). …”
mentioning
confidence: 99%
“…In his study, Freeman (1956) identified as Tae. martis an immature cestode from the nearctic marten, M americana, from Ontario, Canada, on the basis of the form and dimensions of the rostellar hooks, of which large and small measured 146 and 133, respectively.…”
Section: Metacestode (Figs 5 6) Descriptionmentioning
confidence: 99%
“…hydatigena were later more adequately defined by Joyeux and Baer (1936). Freeman (1956) considered the work of Baer (1934, 1936), and noting the large size of rostellar hooks they reported for Tae. intermedia and noting as well that Dubnitskii (1952) had listed Tae.…”
Section: Metacestode (Figs 5 6) Descriptionmentioning
confidence: 99%
“…The exogenous budding in T. crassiceps was studied by Freeman (1962). He also examined T. mustelae, in which a single oncosphere may give rise to more than one metacestode by the formation of multiple scoleces (Freeman 1956). Gvozdev and Agapova (1963) Frank 2000), T. krepkogorski and T. selousi (see below for discussion on the significance of the scolex retraction or invagination).…”
Section: Asexual Multiplicationmentioning
confidence: 99%